Now: A Discourse-Based Theory - Hunter, Julie (Proceedings of the Amsterdam Colloquium, 2011)
In general, now is interpreted as the utterance time and cannot refer to a time made salient in the discourse in the way that a third person pronoun can refer to an individual made salient in the discourse: (1) I like to think about my grandmother. I always had a great time with her. (2) I like to think back on the summer of ’97. I was so happy *now. Yet there are exceptions (cf. Banfield 1982, Hunter 2010, Kamp & Reyle 1993, Lee & Choi 2009, Predelli 1998, Recanati 2004, Schlenker 2004). In the following examples, now denotes a time that lies in the past of the utterance time and is introduced at some prior point in the discourse: (3) Five months later, I sat with her as she lay in bed, breathing thin slivers of breath and moaning... I was alone in her bleak room. Alone, because there was none of her in it, just a body that now held no essence of my mum.1 (4) The letter is marked “personal and private” and is addressed to President Franklin D. Roosevelt’s secretary, Grace Tully, who was with the ailing chief executive in Warm Springs, Ga., that Thursday in 1945. The writer was Lucy Mercer Rutherfurd, who decades before had been FDR’s mistress and who now was making arrangements for what would be their last fateful meeting at the president’s rural retreat.2 (3) is taken from an article in which the author describes her mother’s struggles with Alzheimer’s. Throughout the article, it is clear that the author is recounting past events. Her use of now does not denote the utterance time in any sense; it rather denotes a time in the past at which she visited her ailing mother. The two sentences in (4) are about a letter to FDR that was acquired by the National Archives. The author of the article describes the writing of the letter as an event in the past and clearly distances that event from the time of the acquisition. Still, he can use now to denote the time of the past letter writing event. This paper offers a semantic theory of anaphoric uses of now; that is, uses of now in which now refers to a time introduced in discourse. Contrary to existing theories of now, I argue that the interpretation of an anaphoric use of now is determined by the rhetorical structure of the discourse in which the token of now figures. The details of my theory are presented in Segmented Discourse Representation Theory (Asher & Lascarides 2003).